2020
DOI: 10.1002/prp2.651
|View full text |Cite
|
Sign up to set email alerts
|

Do proton pump inhibitors increase mortality? A systematic review and in‐depth analysis of the evidence

Abstract: Proton pump inhibitors (PPIs) were primarily approved for short‐term use (2 to 8 weeks). However, PPI use continues to expand. Widely believed to be safe, we reviewed emerging evidence on increased mortality with PPI long‐term use. Our 2016 systematic PPI drug class review found that mortality was not reported as an outcome in randomized controlled trials (RCTs) that directly compared different PPIs. We sought more recent and comprehensive data on PPI harm outcomes from research syntheses as a follow‐on. A sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…The inhibition of the efficacy of clopidogrel could increase the risk of thromboembolism and coronary syndrome [25]. Because of impaired vasodilation and ischemic changes associated with PPIs, a number of previous studies have demonstrated an increased risk of cardiovascular diseases related to PPI use [26,27]. A review study described that PPI use was related to excess mortality from cardiovascular diseases in 15/1000 persons [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of the efficacy of clopidogrel could increase the risk of thromboembolism and coronary syndrome [25]. Because of impaired vasodilation and ischemic changes associated with PPIs, a number of previous studies have demonstrated an increased risk of cardiovascular diseases related to PPI use [26,27]. A review study described that PPI use was related to excess mortality from cardiovascular diseases in 15/1000 persons [27].…”
Section: Discussionmentioning
confidence: 99%
“…Because of impaired vasodilation and ischemic changes associated with PPIs, a number of previous studies have demonstrated an increased risk of cardiovascular diseases related to PPI use [26,27]. A review study described that PPI use was related to excess mortality from cardiovascular diseases in 15/1000 persons [27]. As the cochlea is susceptible to ischemic injury due to the high oxygen demands and blood supply from the end artery [10,11], ischemia following PPI use could impact cochlear dysfunction and hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, the US FDA issued warnings about concomitant prescribing of clopidogrel with omeprazole/esomeprazole due to concerns about impaired inhibition of platelet aggregation. The warning did not extend to other PPIs [ 26 ].…”
Section: Ppi Adverse Effectsmentioning
confidence: 99%
“…There may also be an increased risk of cardiovascular and cerebrovascular events linked with chronic PPI treatment, especially among patients prescribed anti-platelet medicines; however, there is conflicting evidence [134][135][136][137][138]. Prescribers may want to keep this in mind when managing patients with GERD and cardiovascular diseases, and pharmacists and their assistants when dispensing PPIs.…”
Section: Potential Overuse Of Ppis and The Implicationsmentioning
confidence: 99%